2019
DOI: 10.1038/s41598-019-53747-5
|View full text |Cite
|
Sign up to set email alerts
|

Methanolic extract of Potentilla fulgens root and its ethyl-acetate fraction delays the process of carcinogenesis in mice

Abstract: People of north-eastern states of India consume raw areca-nut (RAN) and lime which could lead to oral, esophageal and gastric cancers. However, the incidence of these cancers are significantly lesser in those who consume pieces of Potentilla fulgens root along with RAN. Since evaluation of anticancer role, if any, of P. fulgens on RAN-mediated genetic alterations in human is difficult because of other compounding factors, this study was undertaken in mice to focus on gastric carcinogenesis since ad libitum adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Catechin (C 15 H 14 O 6 ; Molecular mass: 290.26) (Figure 1) is a polyphenol compound available in several plants including Potentilla species which has antioxidant activity and is used as a memory enhancer and for lowering the cholesterol in the blood [19][20][21]. In the study conducted by Ganguly et al [22] and Choudhary et al [17] the catechin showed potent anticancer and antioxidant activity respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Catechin (C 15 H 14 O 6 ; Molecular mass: 290.26) (Figure 1) is a polyphenol compound available in several plants including Potentilla species which has antioxidant activity and is used as a memory enhancer and for lowering the cholesterol in the blood [19][20][21]. In the study conducted by Ganguly et al [22] and Choudhary et al [17] the catechin showed potent anticancer and antioxidant activity respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts from some species can also delay the process of carcinogenesis (Ganguly et al. 2019 ; Kowalik et al. 2020 ).…”
mentioning
confidence: 99%